The asymmetric adjustment of global imbalances: Myth or fact? - Neus Dausà; Livio Stracca (European Central Bank (ECB), 2023)
We revisit the so-called "secular international problem", whereby the adjustment of current account imbalances purportedly falls entirely on the shoulders of deficit countries. We introduce a stylised model to rationalise an asymmetric counter-cyclical policy reaction that is stronger for deficit countries. When considering large current account adjustments (both deficits and surpluses) in advanced and emerging economies, we find surprisingly little evidence of greater policy activism in deficit countries. However, large surplus adjustments are less frequent and are associated with export compression, whereas deficit adjustments tend to accompanied by import contraction. Moreover, when we look at current account (terms of trade) shocks we do find some evidence of asymmetry in the sense that fiscal policy is tightened only in reaction to shocks leading to a larger deficit position. Finally, emerging markets display a more counter-cyclical response to negative current account shocks, partly mitigated by the quality of institutions.
Keywords: F32; F41; 330; Current account adjustment; fiscal policy; secular international problem; John Maynard Keynes; Harry Dexter White